125 Assessment of the Effect of Cracked Corn Energy Supplementation on Animal Performance, Rumen Fermentation and Carcass Traits in Grazing Goats during the Winter Months. (1st March 2018) - Abrahamsen, F; Fry, C H; Min, B R; Gurung, N K; Stewart, S; Means, L; Shipp, A; Johnson, R
Abstract: Two years repeated measurement of grazing trials were conducted to determine the effects of cracked corn energy supplementation on animal performance, rumen fermentation and carcass production in grazing meat goats. Thirty-six Kiko wethers in yr. 1 (Capra hircus; initial BW= 18.2 ± 2.11 kg; n=9) and twenty-four Kiko crossbred male goats in yr. 2 (BW = 25.8 ± 1.04 kg; n=6) were randomly assigned to one of the four treatments consisting of treatment 1 (control; no corn supplementation), treatment 2 (0.5% of BW corn supplementation), treatment 3 (1.0% of BW corn supplementation), and treatment 4 (1.5% of BW corn supplementation) during 2 years in 133- and 45-d grazing studies during the winter months, respectively. Animal BW was measured at 28-d intervals and ADG was calculated. Rumen and blood samples were collected, at the end of the trial to assess rumen pH, volatile fatty acids (VFA), rumen ammonia, blood chemistry profiles. Animals were fed cracked corn once a day at 0800 h and had free access to water and a trace mineral salt block. Eight established paddocks, 0.5 acre each was planted winter wheat (Triticum aestivum)/annual rye grass (Lolium multiflorum), where two paddocks represented each treatment. Forage samples were collected monthly starting in February through April to determine forage biomass production and forage chemical analysis with animals grazing. After final BW measurement, all the goats were transported approximately 290 km to the Mississippi State University Meat Science Laboratory, MS for carcass traits according to the USDA approved guidelines. Data were analyzed using the MIXED procedure of SAS. Results showed that there were no differences (P>0.05) in growth performance, ADG, carcass traits, ruminal pH, VFA, and blood profiles among treatments due probably to substitution effects. However, isovalerate and ruminal ammonia levels were higher (P<0.01) for control than for corn supplemented groups in yr 2. The forage biomass and quality were similar among treatments. The results suggested that the high quality winter wheat forage do not require any supplementation during the winter season for growing meat goats. A further investigation is required over the grazing seasons to minimize seasonal variability.